Carbon nanotubes for wound healing: material design, mechanistic insights - Poddar, Nidhi; Naik, Kaustubh; Kumari, Sushma (Frontiers in Bioengineering and Biotechnology, 2026)
Chronic wounds such as diabetic ulcers remain significantly higher in global healthcare burden due to impaired angiogenesis, infection, and sustained inflammation. Carbon nanotubes (CNTs) are promising candidates for advanced wound-dressing applications due to their exceptional electrical conductivity, high mechanical strength, photothermal performance, and ease of surface modification. This review discusses recent progress in their functions in haemostasis, microbial protection, anti-inflammatory regulation, and tissue repair. We discussed research papers on CNT-based multifunctional hydrogels, electrospun scaffolds, and innovative dressings for bioactive agent delivery, electrical stimulation, and real-time monitoring of wound healing. We also discussed in vivo preclinical studies demonstrating significant re-epithelialization and increased angiogenesis, with accelerated wound closure in disease-impaired healing models, such as diabetes. Nevertheless, limitations such as cytotoxicity, impediments to scale-up manufacturing, and regulatory issues hinder direct clinical translation. To overcome these drawbacks, several approaches, such as chemical functionalization, biodegradable CNT derivatives, and hybrid nanocomposites, have been developed. Finally, we describe the translational path for CNT-based wound-healing applications and offer perspectives on future therapeutic interventions for chronic and complex wounds in the context of precision medicine.